Pemanfaatan Lampu Penerangan Sebagai Metode Pengendalian Hama di Ladang Sawah Bawang Masyarakat Dringu Probolinggo: Indonesia - Mas Ahmad Baihaqi; M. Novan Fithrianto; Hartawan Abdillah; Alief , Muhammad; Judi , Suharsono; Mufid , Andrianata (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2025)
Pest control in onion fields has become a major challenge for farmers, particularly in the Dringu area of Probolinggo, where there is a heavy reliance on chemical pesticides. The use of pesticides has negative impacts on the environment and health, while also increasing production costs. This study aims to implement UV and LED lighting technology as a more environmentally friendly and efficient solution for pest control. Through this community service initiative, UV and LED lights were installed at several strategic points in the onion fields with the goal of attracting pest insects and reducing crop damage. The results showed a decrease in pest populations by 30-40%, a reduction in pesticide use by up to 60%, and an improvement in the quality of onion harvests. This technology also provides energy efficiency, reduces long-term operational costs, and enhances agricultural sustainability. Furthermore, the training provided to farmers helped improve their understanding and skills in operating this technology. The application of UV and LED lighting can serve as an effective and sustainable alternative for pest control in the agricultural sector, particularly for onion crops in Dringu